Training Assistant for Automotive Engineering through Augmented Reality. - Pusda Cheza, Fernando Ramiro (2019)
This article proposes the development of an augmented reality appli-cation for mobile devices with Android OS focused on the visualization and in-teraction of the user with the components, technical characteristics, location and the processes of disassembly and assembly of engine in a vehicle; facilitating the learning process referring to this automotive system. The application was devel-oped in the graphic engine 3D Unity and the use of Vuforia for the recognition of objects in 3D, being a technological tool that allows vouching the learning in the internal combustion engine, guiding the user and changing the paradigms of the use of physical manuals with the new technological advances as the aug-mented reality.